Ciencia, exotismo y colonialismo en la Exposición Universal de París de 18781 - Sánchez Gómez, Luis Ángel (Cuadernos de Historia Contemporánea, 2006)
The Exposition Universelle of 1878 has been partially eclipsed in the historiography due to the great public success reached by others exhibitions that took place in Paris before and after that year. However, the 1878 exposition was really important. We make in this article a general revision of the contents of this exposition and we study in a more detailed way three special and outstanding contexts: the “Street of the Nations”, the colonial section and the Archaeology and Anthropology expositions.
Keywords: World’s Fair; Exposition Universelle; Paris; Exoticism; Colonialism; Nationalism; Archaeology; Anthropology